Multidimensional scaling assisted Fourier-transform infrared spectroscopic analysis of fruit wine samples: introducing a novel analytical approach. Issue 32 (31st July 2019) - Kumar, Keshav; Giehl, Anja; Schweiggert, Ralf; Patz, Claus-Dieter
Abstract : The present work introduces a novel classification procedure by combining the multidimensional scaling (MDS) with Fourier transform infrared (FTIR) spectroscopy. Abstract : In the present work, a novel analytical procedure is introduced by combining the multidimensional scaling (MDS) with Fourier transform infrared (FTIR) spectroscopy. MDS analyses are based on distance matrices and hence might serve as a useful and efficient tool to capture subtle spectral compositional differences for classification of the samples. The utility of the proposed analytical procedure is demonstrated by analyzing a collection of seventy-nine fruit wine samples. The obtained classification results were found to correlate well with the differences in their FTIR spectral profiles. In summary, the present work shows that MDS-assisted FTIR spectroscopic analysis can serve as a simple and cost-effective analytical tool to achieve a swift analysis of beverages such as fruit wines.